Photoshop 6 complete (Sybex, 2001)
Photoshop 6 Complete is a one-of-a-kind book--valuable both for its broad content and its low price. This book contains the most comprehensive coverage available of all essential Photoshop features and tasks, from Photoshop fundamentals to tips and tricks for the experienced user.